'An Unimportant River in the Neighbourhood of London': The Use and Abuse of the River Wandle. (November 2015) - Cook, Hadrian
Abstract : Being neither large, nor unusual in its natural attributes, environmental and historical interest in south London's River Wandle lies in the human impact on water quality, habitat modification, maintenance of discharge and physical channel form. Problems emerged during the first half of the nineteenth century deriving from sewage and industrial development, so that between about 1930 and 1970, with the authorities negligent, the river channels became functionally open foul sewers. Recovery since then has included efforts to improve water quality, restore the banks and associated habitats and create enabling initiatives within all economic sectors. This article describes the Wandle's significance as an arena for scrutinizing water resource conflicts since the 1950s, its contribution towards Integrated Water Resources Management and the rise of an urban nature conservation ethos. Questions remain around how — and to what condition — the river might be restored.